2019
DOI: 10.1016/j.scitotenv.2019.03.225
|View full text |Cite
|
Sign up to set email alerts
|

Nitrous acid in marine boundary layer over eastern Bohai Sea, China: Characteristics, sources, and implications

Abstract: Nitrous acid (HONO) serves as a key source of hydroxyl radicals and plays important roles in atmospheric photochemistry. In this study, gaseous HONO and related species and parameters were measured in autumn of 2016 at a marine background site on Tuoji Island in eastern Bohai Sea, China. The HONO concentration in marine boundary layer (MBL) was on average 0.20±0.20 ppbv (average ± standard deviation) with a maximum hourly value of 1.38 ppbv. It exhibited distinct diurnal variations featuring with elevated conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
47
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(60 citation statements)
references
References 51 publications
12
47
0
1
Order By: Relevance
“…Tai meteorological station. These instruments have been widely applied in many previous studies, and the quality assurance and quality control protocols can be found elsewhere [46,[48][49][50]. For CO and O 3 , we performed multi-point calibrations every month and changed the filter every two weeks.…”
Section: Measurement Techniquesmentioning
confidence: 99%
“…Tai meteorological station. These instruments have been widely applied in many previous studies, and the quality assurance and quality control protocols can be found elsewhere [46,[48][49][50]. For CO and O 3 , we performed multi-point calibrations every month and changed the filter every two weeks.…”
Section: Measurement Techniquesmentioning
confidence: 99%
“…An improved empirical formula, Eq. 6, was applied to estimate [OH] using the NO2 and HONO concentrations and the photolysis rate constants (J) of NO2, O3, and HONO (Wen et al, 2019).…”
Section: Hono Photostationary-state Approachmentioning
confidence: 99%
“…Xinken/China Oct.-Nov.,2004 1.60 (Su et al, 2008a) Jinan/China Sep.,2015-Aug.,2016 0.68 (Li et al, 2018) Mar. (Wang et al, 2015) Shanghai/China Aug.2010-Jun.2012 0.70 (Wang et al, 2013) Eastern Bohai Sea/China Oct.-Nov., 2016 1.80 (Wen et al, 2019) Hongkong/China Aug.2011-May, 2012 0.52 (Xu et al, 2015) Kathmandu/South Asia Jan.-Feb.,2003 1.4 (Yu et al, 2009)…”
Section: Competing Interestsunclassified
“…Ring Down Spectrometry (CRDS) (O' Keefe and Deacon, 1988;Scherer et al, 1997;Wheeler et al, 1998), Differential…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the photochemical reaction involving a nitrate series (HNO3, NO3 -) was considered as a major daytime HONO source (Han et al, 2017;Li et al, 2018;Ye et al, 2017;Tsai et al, 2018;Cui et al, 2019). The HONO production reaction is still controversial due to a wide variety of environments involving NOx, RH, and surfaces and incomplete understanding of multi-phase reaction (Bao et al, 2018;Zhang et al, 2019c;Wen et al, 2019;Zhang et al, 2019b). In this context, new approaches are needed to elucidate the HONO formation mechanism.…”
Section: Introductionmentioning
confidence: 99%